Spatio-Temporal Semantic Representation of Cardiac MRI in Heart Attack Patients - Awang Iskandar, D.N.F.; Hamimah, Ujir (2015)
Semantic Web technologies, applications and tools have made great steps forward in the life science and health care data exchange. However, developing appropriate semantic representations, including designing spatio-temporal ontologies, remains difficult and challenging. In this paper, we describe a framework to engineer a spatio-temporal semantic representation for the Cardiac MRI images using the current existing case studies conducted in Sarawak General Hospital Heart Centre.